Carbon nanotubes branch on cobalt oxide nanowires core as enhanced high-rate cathodes of alkaline batteries. Issue 14 (1st October 2018) - Liang, Xinqi; Wang, Fan; Chen, Minghua; Xia, Xinhui
Abstract: Directional synthesis of carbon/metal oxide core-branch arrays is of great importance for development of advanced high-rate alkaline batteries. In this work, we report a facile hydrothermal-chemical vapor deposition (CVD) method for controllable fabrication of Co3 O4 @CNTs core-branch arrays. Interestingly, free-standing Co3 O4 core nanowires are intimately decorated by cocoon-like branch CNTs with diameters of 20–30 nm, which act as a highly conductive network and structure stabilizer. The electrochemical performance of the designed Co3 O4 @CNTs core-branch arrays are tested as cathodes of alkaline batteries. Arising from enhanced electrical conductivity, larger surface area and improved structural stability, the Co3 O4 @CNTs arrays show superior high-rate electrochemical performance with a higher capacity (116 mAh g −1 at 2.5 A g −1 ), lower polarization and better cycling stability than the pure Co3 O4 nanowires arrays (76 mAh g −1 at 2.5 A g −1 ). Our directional composite strategy can be extended to preparation of other carbon-based core-branch arrays for applications in electrochemical batteries and catalysis. Graphical abstract: Self-supported CNTs@Co3 O4 core-branch arrays are prepared by a hydrothermal-CVD method and show good electrochemical performance with high capacity and stable cycling life. fx1